Molecular Mechanisms Associated with ROR1-Mediated Drug Resistance: Crosstalk with Hippo-YAP/TAZ and BMI-1 Pathways - Karvonen, Hanna (Cells, 2019)
Signaling via the Wnt-related receptor tyrosine kinase-like orphan receptor 1 (ROR1) triggers tumorigenic features associated with cancer stem cells (CSCs) and epithelial–mesenchymal transition (EMT), while aberrant expression of ROR1 is strongly linked to advanced disease progression and chemoresistance. Several recent studies have shown that Wnt5a binding to ROR1 promotes oncogenic signaling by activating multiple pathways such as RhoA/Rac1 GTPases and PI3K/AKT, which in turn could induce transcriptional coactivator YAP/TAZ or polycomb complex protein BMI-1 signaling, respectively, to sustain stemness, metastasis and ultimately drug-resistance. These data point towards a new feedback loop during cancer development, linking Wnt5a-ROR1 signaling activation to YAP/TAZ or BMI-1 upregulation that could play an important role in disease progression and treatment resistance. This review focuses on the crosstalk between Wnt5a-ROR1 and YAP/TAZ or the BMI-1 signaling network, together with the current advancements in targeted strategies for ROR1-positive cancers.